Laudato Si' - socioeconomic relevance for a dynamic, shifting, and challenging future - Pavlić, Richard; Rukavina, Bruno, politolog (2021)
The paper deals with the relevance of Laudato Si", five years after its publication. Given the Covid-19 crisis, which triggered the new economic crisis in the world, we believe that Laudato Si" is more relevant in 2020 than it was in 2015. The paper analyzes three socioeconomic segments of Laudato Si" to present its relevance today: mankind and our relationship with others, God and environment, the new economic crisis, and needed global action to comprehend and overcome the Covid-19 crisis. The processes and dangers of five years ago have not disappeared, they have only changed form. Thus, Laudato Si" is not only relevant but can be used as a socioeconomic reconstruction program for Covid-19 aftermaths.
Rad se bavi relevantnošću enciklike Laudato si" pet godina nakon njezina objavljivanja. S obzirom na koronakrizu, koja je pokretač nove ekonomske krize u svijetu, vjerujemo da je enciklika Laudato si" relevantnija u 2020. godini nego 2015. godine. Rad analizira tri socioekonomska segmenta enciklike Laudato si" kako bi se prikazala njezina važnost danas: čovječanstvo i naš odnos s drugim ljudima, Bogom i okolišem, nova kriza u gospodarstvu i nužnost globalne akcije za razumijevanje i prevladavanje koronakrize. Procesi i opasnosti od prije pet godina nisu nestali, nego su samo promijenili oblik. Dakle enciklika Laudato si" nije samo relevantna već se njome može koristiti i kao programom socioekonomske obnove za posljedice koronakrize.
Bibliografske bilješke uz tekst ; bibliografija: str. 203-207.
Summary ; Sažetak.
Keywords: Laudato si’; Enciklike -- Koronakriza -- Zaključavanje -- Ekonomski sustav -- Antropocentrizam; Franciscus, papa -- Papa Franjo